IDENTIFYING THE POTENTIAL YIELD OF SOYBEAN GENOTYPE IN TIDAL LAND TYPE C - Susanto, Gatut Wahyu Anggoro; Putri, Pratanti Haksiwi (Biosaintifika: Journal of Biology & Biology Education, 2019)
Identification of soybean genotypes including potential yield character is a base to understand soybean growth, development, and productivity on potential lands. The purpose of this research is to determine the potential yield of soybean genotype in tidal land type C and their supporting components. Four soybean genotypes and two comparative varieties Anjasmoro and Lawit (adaptive tidal land) were tested on tidal land type C at four locations (three locations in Jambi Province and one location in South Kalimantan Province), July 2017. The research was conducted using a randomized design for each location and repeated four times. The plot size was 12 m2, spacing row 40 cm x 15 cm, two plants for each hole. GH_KR_13, GH_GR_1 and  GH_GR_5 productivity equal with Lawit, the adaptive variety for tidal land type C. While, Anjasmoro showed more than 2.20 t/ha in seeds productivity, 54 filled pod for each plant, with large size of seeds (15.84 gram/100 seeds). Anjasmoro had higher seed productivity than all of genotypes including Lawit. Anjasmoro with it?s potential yield and productivity, can become farmer preferences and deserve to be developed in tidal land type C.